2007
DOI: 10.1002/polb.21129
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization behavior of poly(butylene adipate‐co‐terephthalate)/clay nano‐biocomposites

Abstract: The study of the nonisothermal crystallization behavior of layered silicates micro‐ and nano‐biocomposites based on poly(butylene adipate‐co‐terephthalate) (PBAT), a biodegradable copolyester, has been carried out with different theoretical models. They were applied and developed with the aim to describe and better understand the influence of the layered silicates dispersion on crystallization. The nucleation efficiency of the layered silicates has been demonstrated with the use of the “Modified Avrami model,”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
28
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 21 publications
12
28
0
1
Order By: Relevance
“…The fillers can act as heterogeneous nucleation sites (Fig. 2), increasing the crystallinity of the PBAT [86,87]. The increase in crystallinity is usually associated with improved mechanical properties of the polymers [73,84,88,89], however, this relation is not always linear.…”
Section: Pbat-based Compositesmentioning
confidence: 99%
“…The fillers can act as heterogeneous nucleation sites (Fig. 2), increasing the crystallinity of the PBAT [86,87]. The increase in crystallinity is usually associated with improved mechanical properties of the polymers [73,84,88,89], however, this relation is not always linear.…”
Section: Pbat-based Compositesmentioning
confidence: 99%
“…These early works were expanded by Chivrac et al [13,14] who tested various organoclays, such as C20A, D43B and N804 and compared the solvent and melt intercalation elaboration processes. The resulting materials structure and properties were compared to neat PBAT and to PBAT/MMT-Na, the composites with non-modified montmorillonite.…”
Section: Preparation Of Nano-biocomposites Based On Pbat Aliphatic-armentioning
confidence: 98%
“…No impact of the clay dispersion has been observed on the Tg and Tm values, whereas the crystallinity showed decreasing values when increasing the clay content for both unmodified and organomodified clays. Thus, authors investigated more in details the influence of the clay dispersion on the PBAT non-isothermal crystallization [14] and it was concluded that addition of a small amount of MMT enhances the PBAT nucleation mechanism, but also that the dispersed clay platelets hinder the crystallites growth. These two antagonist phenomena may lead to different PBAT crystallization behaviour depending on the clay dispersion.…”
Section: Preparation Of Nano-biocomposites Based On Pbat Aliphatic-armentioning
confidence: 98%
“…Someya et al, (2004Someya et al, ( ,2005 [12,13] obtained certain level of clay intercalation and exfoliation in several compositions of PBAT/clay nanocomposites prepared by melt intercalation. Chivrac et al, (2006Chivrac et al, ( , 2007 [14,15] have tested some commercial montmorillonites in PBAT compositions, revealing that higher intercalation degrees could be obtained by using particular preparation techniques and that the stiffness of PBAT matrix could increase with clay content due to the important interactions between PBAT and nanoparticles. In a recent work [16][17][18], we studied the morphology and properties of PBAT nanocomposites prepared by meltmixing and by using different amount and types of nanoparticles including montmorillonite, fluorohectorite, and sepiolite.…”
Section: Introductionmentioning
confidence: 99%